Ocular adnexal marginal zone lymphoma arising in a patient with IgG4-related ophthalmic disease. Issue 2 (4th March 2019) - Nishida, Kenji; Sogabe, Yuka; Makihara, Ayako; Senoo, Akemi; Morimoto, Hisanori; Takeuchi, Mai; Gion, Yuka; Yoshino, Tadashi; Sato, Yasuharu
Abstract: A 41-year-old man was diagnosed with immunoglobulin G4-related disease (IgG4-RD) in both eyelids 4 years ago and exhibited good response to steroid therapy. However, rapid swelling of the right eyelid lesion was recently observed. As IgG4-RD progression was suspected, biopsy was performed. Although the histology was consistent with IgG4-RD, the infiltrating large atypical lymphoid cells showed immunoglobulin light-chain restriction and IgH gene rearrangement. Consequently, he was diagnosed with extranodal marginal zone lymphoma with abundant IgG4-positive cells.